Management of Islamic Philanthropy-Based Education Financing in Increasing Access to Free Education for Orphans Children - Aqli Qosyim, Roshiful; Zarkasyi, Ahmad (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
The article describes the management of Islamic philanthropy-based education financing in increasing access to free education for orphans and poor children at the Raudhatul Ulum Islamic boarding school, Sumberanyar Village, Lumajang Regency, East Java. This research uses qualitative research obtained by researchers based on data in the field. The research period starts from December 2023 to February 2024. The data source in this research is primary data obtained through interviews and direct observation with informants. The data analysis steps used in this research are the Interactive Analysis Model from Miles and Huberman: data reduction, data display, and conclusion drawing. Based on the research results after being dialogued with the results of the conceptual study, it can be described as Islamic philanthropy-based education financing management in Islamic boarding schools. Raudhatul Ulum Lumajang Regency includes three activities: planning sources of philanthropy-based education financing (waqf and infaq), allocating and distributing philanthropic fund financing, and monitoring and accountability (auditing) of philanthropic funds.